Surface Modification of TiO2 for Obtaining High Resistance against Poisoning during Photocatalytic Decomposition of Toluene - Byeong Jun Cha (Catalysts, 2018)
Titanium oxide (TiO2) nanostructures, the most widely used photocatalysts, are known to suffer from poisoning of the active sites during photocatalytic decomposition of volatile organic compounds. Partially oxidized organic compounds with low volatility stick to the catalyst surface, limiting the practical application for air purification. In this work, we studied the UV-driven photocatalytic activity of bare TiO2 toward toluene decomposition under various conditions and found that surface deactivation is pronounced either under dry conditions or humid conditions with a very high toluene concentration (~442 ppm). In contrast, when the humidity was relatively high (~34 %RH) and toluene concentration was low (~66 ppm), such deactivation was not significant. We then modified TiO2 surfaces by deposition of polydimethylsiloxane and subsequent annealing, which yielded a more hydrophilic surface. We provide experimental evidence that our hydrophilic TiO2 does not show deactivation under the conditions that induce significant deactivation with bare TiO2. Conversion of toluene into dimethylacetamide was observed on the hydrophilic TiO2 and did not result in poisoning of active sites. Our hydrophilic TiO2 shows high potential for application in air purification for extended time, which is not possible using bare TiO2 due to the significant poisoning of active sites.